Long‐Distance Asthenospheric Transport of Plume‐Influenced Mantle From Afar to Anatolia. (1st February 2023) - Hua, J.; Fischer, K. M.; Gazel, E.; Parmentier, E. M.; Hirth, G.
Abstract: The origin of widespread volcanism far from plate boundaries and mantle plumes remains a fundamental unsolved question. An example of this puzzle is the Anatolian region, where abundant intraplate volcanism has occurred since 10 Ma, but a nearby underlying plume structure in the deep mantle is lacking. We employed a combination of seismic and geochemical data to link intraplate volcanism in Anatolia to a trail of magmatic centers leading back to East Africa and its mantle plume, consistent with northward asthenospheric transport over a ∼2, 500 km distance. Joint modeling of seismic imaging and petrological data indicates that the east Anatolian mantle potential temperature is higher than the ambient mantle (∼1, 420°C). Based on multiple seismic tomography models, the Anatolian upper mantle is likely connected to East Africa by an asthenospheric channel with low seismic velocities. Along the channel, isotopic signatures among volcanoes are consistent with a common mantle source, and petrological data demonstrate similar elevated mantle temperatures, consistent with little cooling in the channel during the long‐distance transport. Horizontal asthenospheric pressure gradients originating from mantle plume upwelling beneath East Africa provide a mechanism for high lateral transport rates that match the relatively constant mantle potential temperatures along the channel. Rapid long‐distance asthenospheric flow helps explain the widespread occurrence of global intraplate magmatism in regions far from deeply‐rooted mantle plumes throughout Earth history. Plain Language Summary: Volcanoes that exist in the middle of tectonic plates are often thought to be produced by plumes of high temperature mantle that originate deep within the Earth, near the core‐mantle boundary. However, while many of these "intraplate" volcanoes share chemical compositions with plume‐related volcanism, their close connection to a deep mantle upwelling is not clear for all locations. In this study, we jointly analyze images of the Earth's interior structure from earthquake waves and the chemical properties of erupted magmas to make the case that: (a) the volcanoes in the Anatolia region are fed by a mantle plume that lies beneath the East African Rift system, and (b) upper mantle is transported horizontally over ∼2, 500 km from Africa to Anatolia without significant cooling. We modeled mantle transport driven by a hot upwelling mantle plume and found that it is fast enough to explain the apparent lack of cooling. These results suggest that mantle plumes can affect a much larger volume of the Earth than is commonly assumed. Key Points: Upper mantle partial melting prevails beneath the Anatolian region based on seismic receiver functions Plume‐originated asthenosphere is transported from East Africa to Anatolia while preserving elevated temperature based on basalt samples Transport over ∼2, 500 km is facilitated by reduced viscosity due to high temperature and possibly takes only ∼10 Myr